Efficacy and Tolerability of Short-Term Hormonal Therapy Following Conservative Surgery for Endometriosis: Efficay and Clinical Tolerability of Short-Term Hormonal Treatment for Endometriosis Pain - Trisetiyono, Yuli; Sarastry, Razmaeda; Dewantiningrum, Julian; Anityo Mochtar, Arufiadi; Kristanto, Herman; Thaufik Hidayat, Syarief (Indonesian Socety of Obstetrics and Gynecology, 2025)
AbstractObjective: To compare the efficacy and tolerability of four short-term hormonal therapies; Dienogest (DNG), Depot Medroxyprogesterone Acetate (DMPA), continuous Combined Oral Contraceptive (COC), and Leuprolide Acetate (LA); administered for 12 weeks after conservative endometriosis surgery. Methods: This randomized, prospective, open-label study enrolled reproductive-aged women with surgically confirmed endometriosis. Participants were randomly assigned to receive DNG 2 mg daily, DMPA 150 mg intramuscularly every 12 weeks, continuous COC (ethinyl estradiol 0.03 mg and levonogestrel 0.15 mg) daily, or LA 3.75 mg intramuscularly every 4 weeks. Primary outcomes were changes in pain intensity (visual analog scale, VAS), hormonal markers (estradiol, E2), inflammatory markers (TNF-?), and the Menopause Rating Scale (MRS) as an indicator of tolerability. Data were analyzed using ANOVA with a significance level of p < 0.05. Results: All four regimens resulted in significant reductions in dysmenorrhea, dyspareunia, and chronic pelvic pain after 12 weeks (p < 0.001). E2 and TNF-? levels decreased significantly in all groups, with the greatest decline observed in the LA arm. No significant differences were found among regimens in pain reduction or biomarker changes (p > 0.05). MRS scores increased transiently at week 8, particularly in the LA group, reflecting hypoestrogenic effects, but decreased by week 12 in all groups. Conclusion: Short-term postoperative hormonal therapy with DNG, DMPA, COC, or LA effectively reduces pain and inflammatory markers following endometriosis surgery. Progestin-based therapies achieve comparable clinical efficacy to GnRH agonists with superior tolerability. Individualized selection based on symptom profile, side effects, and accessibility is recommended in accordance with ESHRE guidelines. Keywords: endometriosis-associated pain, Menopause Rating Scale, short-term hormonal therapy.